Creating Joyful Learning Through Snowball Throwing to Enhance Primary Students’ Vocabulary - Tasaufi, Bila Nastiti; Herwiana, Sakhi; Novitasari, Nine Febrie (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The teaching of English has some challenges, especially in primary school. The primary students do not speak English as their mother language, therefore it is quite difficult for them to acquire English fluently. Additionally, English in Indonesia is a foreign language that the children do not use in their daily life, particularly in rural areas. The preliminary study found that the primary students’ English score was under the minimum passing criteria which was 68, there was only thirty-four percent (34%) of students can achieve it. Thus, the use of teaching techniques was implemented to help the children to acquire better English. The purpose of this study was to examine how a snowball-throwing teaching method and youtube may be used to improve the vocabulary understanding of fifth graders. This study used collaborative classroom action research (CCAR). The results showed that the snowball throwing method and youtube can help students improve their vocabulary knowledge. Vocabulary tests got an average score of 93.6, with ninety-eight percent (98 percent) of students reach with the criteria. They were enthusiastic about utilizing this method to learn English. They were also able to work well in groups, and displayed excellent teamwork skills.